Laut Dalam Perspektif Teologi Hindu Pada Susastra Jawa Kuno - Suarka, I Nyoman; Pratama, Putu Ari Suprapta; Suastika, I Made; Diah Savitri, Putu (Jurnal Penelitian Agama Hindu, 2024)
The ocean is in an increasingly severe ecological crisis, which has an impact on the crisis of the universe at large. The attitude of people who are increasingly moving away from tradition and traditional sources of reference and prioritizing worldliness is thought to be one of the causes of the marine crisis. Therefore, efforts to encourage people to manage the sea more wisely must continue to be encouraged. This article aims to examine the local wisdom of the sea in ancient Javanese literature from the perspective of Hindu theology and to contribute to raising public awareness through a more complete and comprehensive understanding of the sea. The method used in the research is a qualitative method using Old Javanese literary texts as the main data source. The reading method was used in data collection assisted by the techniques of script transfer, language transfer, and recording. Data analysis was carried out by applying the content analysis method based on the working principles of semiotic theory. The result found is that the narrative of the sea in Old Javanese literature has a Hindu theological dimension. The sea is understood in a cross-section of Hindu theology starting with the awareness of the Impersonal God (Nirguna Brahman) by calling God Sang Hyang Adisuksma, towards the awareness of the Personal God (Saguna Brahman) by calling God as Lord Baruna, worshiped as an istadewata whose role is to control the laws of the universe (rta). The sea (segara) is glorified as a pair of mountains (giri) in the conception of segara-giri is a sacred axis in Hindu life, both as a source of life, a source of disaster and disease and a source of liberation. The theological construction of Old Javanese literature is imbued with Hindu theology as mandated by the Vedas.